Polycentric LocAl Led Climate AdapTation ChampION (ACTION) to build resilience to droughts in Hanzila Village, Southern Zambia - Mweemba, C. E.; Amarnath, Giriraj; van Koppen, Barbara (International Water Management Institute, 2023)
As part of the "ClimBeR: Building Systemic Resilience Against Climate Variability and Extremes" initiative, the Zambia spotlight developed a case study on "Water Access and Management in Community-based Water Tenure" in two rural communities of Zambia. The study highlighted insights into bottom-up, topdown polycentric decision-making processes that people come up with to advance local solutions to preclude challenges from the risks and impacts of climate change around the interconnectedness of water, food, and land for sustainable livelihood development and reduce people's vulnerabilities (Mweemba et al. 2023). Aside from local solutions, the study highlighted the role of external support in enhancing adaptive community capacities to respond to the impacts of climate change. This highlighted the importance of mobilizing workable solutions into next-layer interventions, such as external financing for water infrastructure through vertical and horizontal integration processes. Of significant relevance for this project stage, the Case Study on Water Access and Management in Community-based Water Tenure recommendations pointed to investment in public water infrastructure, such as boreholes, to ensure extensive coverage of people accessing water resources. Prioritizing the development of water infrastructure equally contributes to equitable access to water for drinking, domestic and productive uses and guarantees communal tenure in the ownership, access and use of communally owned sources. With recurrent droughts and uncertainty resulting from extreme weather events, investment in water provides opportunities for communities to have reliable water sources that open up opportunities for food security through small-scale crop farming activities and livestock watering, especially when and where other reliable water sources dry up due to droughts or cannot be accessed due to excessive flooding. Following up on these recommendations, ClimBeR’s LocAlly Led Climate AdapTation ChampION (ACTION) Grant Program focused on interventions driven and implemented at the local level in Hanzila community, with the involvement and leadership of community members, organizations, and local governments. For example, initial stages involved initiating collaborations with the community in Hanzila community project goals which was by followed by diagnosing of challenges resulting from impacts of climate change within the community and determining appropriate solutions for community adaptation. These interventions were tailored to the community's specific needs, priorities, and context and aimed to build resilience against the impacts of climate change. As such, the ACTION project was initiated to develop a water infrastructure for a community to build community resilience to climate change adaptation through a champion community-led project. The community of Hanzila collaborated with the ACTION Grant Program and the local authorities to pursue funding opportunities to respond to the community-identified water infrastructure requirement to fulfil their water needs. As a result of the CGIAR ClimBeR initiative, the ACTION Grant program financed the budgetary requirement of installing a solar borehole infrastructure within the community. The project highlighted the significant horizontal and vertical polycentric decisions by community members in advancing local solutions to improve access to water and the role played by government and donors in polycentric decision-making processes in providing solutions for improved access to water for drinking, domestic and productive uses.